Effectiveness and response differences of a multidisciplinary workplace health promotion program for healthcare workers - Cheng, Kai-Hung; Wu, Ning-Kuang; Chen, Chao-Tung; Hsu, Chih-Yu; Lin, Yen-An; Luo, John Jiin-Chyuan; Lee, Li-Ang; Chuang, Hai-Hua (Frontiers in Medicine, 2022)
Background: Workplace health promotion (WHP) in the healthcare industry is an important yet challenging issue to address, given the high workload, heterogeneity of work activities, and long work hours of healthcare workers (HCWs). This study aimed to investigate the effectiveness and response differences of a multidisciplinary WHP program conducted in HCWs. Methods: This retrospective cohort study included HCWs participating in a multidisciplinary WHP program in five healthcare facilities. The 20-week intervention included multiple easy-to-access 90-min exercise classes, one 15-min nutrition consultation, and behavioral education. Pre- and post-interventional anthropometrics, body composition, and physical fitness (PF) were compared with paired sample t-tests. Response differences across sex, age, weight status, and shiftwork status were analyzed with a generalized estimating equation. Results: A total of 302 HCWs (mean age, 37.2 ± 9.5 years; 281 (93.0%) females and 21 (7.0%) males) were analyzed. The intervention effectively improved all anthropometric (body mass index, waist circumference, waist-hip ratio, and waist-to-height ratio), body composition (body fat percentage, muscle weight, visceral fat area), and PF (grip strength, high jump, sit-up, sit-and-reach, step test) parameters in all participants (all p < 0.05). Subgroup analyses revealed shift workers had a more significant mean reduction in body mass index than non-shift workers (adjusted p = 0.045). However, there was no significant response difference across sex, age, and weight subgroups. Conclusions: This study suggested that a multidisciplinary WHP program can improve anthropometric and PF profiles regardless of sex, age, and weight status for HCWs, and shifter workers might benefit more from the intervention.